Vaccination budget in Europe: an update - Olivier Ethgen; Vanessa Rémy; Katherine Wargo (Taylor & Francis Group, 2018)
Immunization has been shown to be the most effective disease prevention measure of all time, apart from water purification. However, vaccination programs remain highly vulnerable to budget cuts as their benefits may not be immediately and fully identifiable. Therefore, monitoring of healthcare expenditures allocated to prevention and vaccination is critical. This letter updates our previous observation of expenditure for prevention and vaccination programs in eight European countries by adding data from 2014, where available. Prevention and vaccines still entail a relatively low level of investment in European countries. Less than 0.5% of GDP is allocated to disease prevention programs and vaccine expenditure fall below 0.5% of healthcare spending in many of the countries. An adequate level of resources needs to be allocated to ensure efficient and sustainable vaccination programs.